Perceived duration of Visual and Tactile Stimuli Depends on Perceived Speed - Tomassini, Alice; Gori, Monica; Burr, David; Sandini, Giulio; Morrone, Concetta (Frontiers in Integrative Neuroscience, 2011)
It is known that the perceived duration of visual stimuli is strongly influenced by speed: faster moving stimuli appear to last longer. To test whether this is a general property of sensory systems we asked participants to reproduce the duration of visual and tactile gratings, and visuo-tactile gratings moving at a variable speed (3.5 – 15 cm/s) for three different durations (400, 600 and 800 ms). For both modalities, the apparent duration of the stimulus increased strongly with stimulus speed, more so for tactile than for visual stimuli. In addition, visual stimuli were perceived to last approximately 200 ms longer than tactile stimuli. The apparent duration of visuo-tactile stimuli lay between the unimodal estimates, as the Bayesian account predicts, but the bimodal precision of the reproduction did not show the theoretical improvement. A cross-modal speed-matching task revealed that visual stimuli were perceived to move faster than tactile stimuli. To test whether the large difference in the perceived duration of visual and tactile stimuli resulted from the difference in their perceived speed, we repeated the time reproduction task with visual and tactile stimuli matched in apparent speed. This reduced, but did not completely eliminate the difference in apparent duration. These results show that for both vision and touch, perceived duration depends on speed, pointing to common strategies of time perception.